Why Do Entrepreneurs Quit the Business? A Study of Disengagement and its Implications - Windreis, Christ (Westscience Press, 2025)
Entrepreneurial exit is a little-studied yet foundational element of the entrepreneurial life cycle, involving both voluntary and involuntary termination of business ownership. This research performs a systematic review of 25 Scopus-listed articles to investigate factors driving entrepreneurial exits and their consequences. The results identify the interaction of internal, organizational, and external factors in determining exit choices. Personal motives, such as economic aspirations and balance between work and personal life, drive exits, and organizational performance and market circumstances have a part in shaping results. The study indicates significant categories of exits, such as strategic and reactionary, and their meanings for entrepreneurs, companies, and economies. The findings emphasize the need for forward-thinking exit plans, facilitating policies, and further study on cultural and contextual dimensions. This integrated review contributes to the knowledge of entrepreneurial exit, providing valuable insights for policymakers, practitioners, and academics in promoting sustainable entrepreneurship.